Priložnosti in pasti umetne inteligence v pastorali - Šegula, Andrej (Bogoslovni vestnik, 2024)
Throughout history, the Catholic Church has been aware that it is part of this world. It has tried to use all its acquisitions for the good of the pastoral. Modern technologies, new media have entered into every pore of the modern world. From the very beginning, the Church has also been aware of the dangers. For this reason, it has acted more or less cautiously. On the other hand, it has also sought entry points. Since the Second Vatican Council, we have a number of documents that give guidance. Having said all this, we must not ignore the covid period, which accelerated the use of these. Overnight, media that were considered ‘dangerous’ became ‘desirable’. In some parts of the world, AI is becoming an integral part of life, and therefore of the pastoral. We want to present the opportunities that AI brings, as well as the dangers and pitfalls in the context of the contemporary pastoral.
Keywords: artificial intelligence (AI); Church documents; dokumenti Cerkve; modern technologies; opportunities; pasti; pastoral; pastorala; pitfalls; priložnosti; sodobne tehnologije; umetna inteligenca (UI)